PSYCHOLOGY OF FAMILY AND FAMILY RELATIONS - Abdurahimov Shokosim (Galaxy International Interdisciplinary Research Journal, 2022)
This article is about family division. Marriage and family. Family functions. Family structure. Stages of the family life cycle. The subject of family psychology is the functional structure of the family, the main patterns and dynamics of its development; the development of personality in the family.